A School at the Center Study II. - Mid-Continent Regional Educational Lab., Aurora, CO.; Mid-Continent Regional Educational Lab., Aurora, CO. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
This report, which focuses on improving education in rural Nebraska, grew out of a 2-week teachers' institute held in Walthill, Nebraska, in June 1993. "Introduction: The Vision of Community-Based Schools and the Future of Rural Places" (Toni Haas, Paul Nachtigal) examines current civic and social trends in rural communities and the role that schools could have in revitalizing communities and improving the quality of rural life. This chapter also discusses the benefits of small community schools in which students plan what to learn and how to demonstrate and evaluate their accomplishments. "The Implementation of the Vision in Rural Nebraska" (Paul A. Olson) addresses the depopulation of rural communities in Nebraska and the impact this trend has had on rural schooling. "The Abandonment of the Small School and the Need for Reviving It" (Jim Walter) compares large and small schools in terms of school financing, curriculum changes and quality, student achievement, and student development opportunities. It concludes that bigger schools are not better at providing a superior education, and that there are numerous benefits to small, rural schools. "Schools and Rural Culture: Arts and Humanities Issues" (Paul A. Olson) offers strategies for enhancing the curriculum, including activities in which students investigate their family history, their town or ethnic group, and the cultural character of the immediate region. "Education as a Tool for Economic and Environmental Development in the Sustainable Community" (Rose Jasperson, Jan Stansberry) describes successful economic development operations based in public schools. Chapter 6 provides an instructional framework for developing community-based learning units and describes nine teacher-developed units that integrate various academic areas and community study. The last chapter provides a bibliography of historic places in northeast Nebraska, resources for exploring sustainable agriculture and economic development, and a questionnaire for preparing teachers and community members for community-based education. (Contains 59 references.) (LP)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Schools; Curriculum Development; Economic Development; Elementary Secondary Education; Learning Activities; Local History; Program Descriptions; Rural Education; Rural Schools; School Community Relationship; School Size; Small Schools; Small Towns; Sustainable Development; Units of Study; Nebraska; Rural Culture; Collected Works, General; Tests/Questionnaires.